2021
DOI: 10.1037/trm0000302
|View full text |Cite
|
Sign up to set email alerts
|

Intersectional trauma: COVID-19, the psychosocial contract, and America’s racialized public health lineage.

Abstract: This comparative review explores how, during COVID-19 and recent American public health disasters, including the water crisis in Flint, Michigan, Hurricane Katrina, and Hurricane Maria, early failures in public health communications, porous epidemiologic oversight, and lax crisis management created significant gaps in outreach and treatment for historically disenfranchised racial/ethnic minorities. In consideration of each event’s broader specter in terms of population health inequities, a highly salient but u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
(92 reference statements)
1
15
0
Order By: Relevance
“…Cost et al ( 2021) also found the rates of deterioration were greatest for those with a pre-existing diagnosis and among children who perceived greater stress from being socially isolated. This is consistent with other cross-sectional studies examining COVID-19 in children and youth with pre-existing mental health problems as well as other pre-existing vulnerabilities like physical health problems (Hawke et al 2020), neurodevelopmental conditions (e.g., Asbury et al 2020;Sciberras et al 2020;Theis et al 2021), and those living in adverse socio-economic circumstances (Whitehead et al 2021) and in racialized communities (Ezell et al 2021). There is nothing new here, differential exposure and vulnerability have been reliably associated with differential outcomes (Cicchetti and Rogosch 1996).…”
Section: Child and Youth Mental Health During The Pandemicsupporting
confidence: 89%
“…Cost et al ( 2021) also found the rates of deterioration were greatest for those with a pre-existing diagnosis and among children who perceived greater stress from being socially isolated. This is consistent with other cross-sectional studies examining COVID-19 in children and youth with pre-existing mental health problems as well as other pre-existing vulnerabilities like physical health problems (Hawke et al 2020), neurodevelopmental conditions (e.g., Asbury et al 2020;Sciberras et al 2020;Theis et al 2021), and those living in adverse socio-economic circumstances (Whitehead et al 2021) and in racialized communities (Ezell et al 2021). There is nothing new here, differential exposure and vulnerability have been reliably associated with differential outcomes (Cicchetti and Rogosch 1996).…”
Section: Child and Youth Mental Health During The Pandemicsupporting
confidence: 89%
“…The pandemic’s burden on mental health is associated with multiple intersecting factors, including economic decline resulting in increased job insecurity [ 3 , 4 ]; housing precarity [ 5 , 6 ]; childcare disruptions and school closures [ 7 , 8 , 9 ]; increased risk of interpersonal violence [ 10 , 11 ]; and general disruption to daily routines [ 12 ]. Furthermore, the burden of COVID-19 disease, and its psychosocial sequelae, has disproportionately impacted certain populations, such as children and youth [ 12 , 13 ], cisgender women [ 14 , 15 , 16 ], minoritized communities [ 17 , 18 ], people who use drugs [ 19 ], older adults [ 20 , 21 ], people with disabilities [ 22 , 23 ], and LGBTQIA+ individuals [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 The galvanising of the Black Lives Matter (BLM) movement during the height of the pandemic with the tragic killing of the African-American George Floyd, due to police brutality on 25 May 2020, gave another layer of understanding the pandemic as 'racialised'. 17 These events redirected examination of the role of structural racism in society, including within healthcare services, an issue that particularly affects people with SCD. 18 It is against this background that we conducted our study.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%